Histopathological audit of nephrectomy specimens from a single center in North India - Bansal, Manishi; Jindal, Ankush; Gupta, Smriti (Eastern Journal of Medical Sciences, 2020)
Introduction: Nephrectomy is a common surgical procedure for wide variety of renal diseases, including both benign and malignant conditions. The causes of nephrectomy may vary with different geographical areas and institutions. A thorough histopathological analysis of nephrectomy specimens abets formulation of treatment guidelines specific to the geographic area. Objective: The objective of the study was to analyze trends and patterns of renal diseases requiring nephrectomy and to observe variations from the conventional pattern or geographic variation, if any. Methods: A hospital-based study was carried out to study and analyze histopathology of 38 nephrectomies done during the period of 2 years (January 2018–December 2019) at Mayo Super Specialty Hospital, Mohali, Punjab. Results: Out of 38 nephrectomies, 20 were benign and 18 were malignant. Malignant lesions were more prevalent in older age groups. Chronic pyelonephritis was most common cause of benign lesions. We observed loss of corticomedullary junction and dilatation of pelvicalyceal system in more than 80% of cases. Among malignant conditions, clear cell renal cell carcinoma was the most common histology. The World Health Organization/the International Society of Urological Pathology Grade 1 was the most common among the malignant lesions and only one case of sarcomatoid differentiation (Grade 4) was seen. Conclusion: The present study provides a detailed histopathological analysis of nephrectomies done at our institute and gives a reflection of the clinical spectrum in this part of India.